(untitled) (Bangladesh Medical Journal, 2014)
A cross sectional study was carried out in the Department of Pathology, Dhaka Medical College, Dhaka and Department of hepatology, Bangabandhu Sheikh Mujib Medical University (BSMMU) during the period of July 2007 to June 2009. Total 55 adult subjects of both sexes were included in this study to evaluate the histological pallern of nonalcoholic fatty liver disease (NAFLD) and its relation with demographic variables including age, sex, BMI, obesity and waist circumference. NAFLD is characterized by macrovesicular deposition of fat in liver. It is now days recognized as a major cause of liver disease and has the propensity for progression to fibrosis and cirrhosis. Study subjects with bright echogenic liver on ultrasonography with no history of alcohol consumption and without having hepatitis B and hepatitis C infections were included. All of them undergone liver biopsy and H&E and Masson’s Trichrome stain slides were examined to evaluate the grade and stage of lVAFLD. Scoring and semiquantitative assessment of steatosis and NAFLD severity was done according to Kleiner scale known as NAFLD Activity Score (NAS). Among the subjects 24 were male and 31 female. Mean age 41±10. 66 years (range 20 - 65 years), BMI 29.13±3. 79 kg/m2 (range 24.22 - 39.00 kg/m2), mean of male waist circumference 92.03±6.75 cm (range 88-109 cm) and mean of female waist circumference was 90.17±6.6cm (range 80-102 cm). Only BMI correlated significantly with NAS score whereas age, BMI and waist circumference of male and female subjects correlated significantly with stage of fibrosis. The study concludes that in developing countries like Bangladesh the incidental finding of NAFLD is increasing because of change in life style and food habit. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18508 Bangladesh Medical Journal 2011 Vol.40(2): 36-40